What Brexit means - Horder, Max, author.
1 online resource
Keywords: What Brexit Means explores the rise of populism in Britain. Drawing on several years of ethnographic fieldwork amongst ideologically committed Brexit activists, it examines the discourse of populism across language, culture, politics, psychology, and cognition. It explains how populism is expressed in terms of ritually renewing social order and solidarity. Rejecting the notion that the territory of populism studies belongs to political science, this book shows how it is in the realm of anthropology - myth, ritual, alterity, consciousness, selfhood - that we witness the most compelling examples of how a phenomena as modern as populism depends upon the same symbolic logics that we find in the premodern world. What Brexit Means is a demonstration of the power of anthropology to explain momentous and poorly predicted transformations in the global order. It will become a benchmark text for those eager for anthropology's contribution to understanding the political turbulence that is rocking the stability of Western democracies.